Immunoprecipitation of antigen-associated [32P]-labelled nucleic acids from Crohn's disease mesenteric lymph nodes. - Butcher, P. D. (1985)
The methods of immunoselection and electrophoretic analysis of [32P]-labelled nucleic acids have been applied to the problem of defining Crohn's disease (CD) specific antigen associated DNA or RNA, with the intention of identifying a presumptive aetiological microbial agent. Mesenteric lymph node derived cells from CD and control gastrointestinal disease cases were cultured in vitro with [32P] orthophosphate after mitogenic stimulation with phytohaemaglutinin and pokeweed mitogen. Total cell lysates were immunoprecipitated with CD and control serum IgG fractions and immune complexes recovered with pansorbin. Antigen associated [32P]-labelled nucleic acids were phenol/chloroform extracted and analysed by electrophoresis on polyacrylamide and agarose gels. No immunoprecipitated nucleic acid specific to CD tissues could be detected and no differences in antigen recognition between CD and control serum IgG were observed. No evidence was obtained for nucleic acid containing antigens either of the autoimmune type or of possible viral or microbial origin in CD mesenteric lymph nodes.